2013
DOI: 10.1002/pc.22403
|View full text |Cite
|
Sign up to set email alerts
|

Role of calcium stearate as a dispersion promoter for new generation carbon black‐organoclay based rubber nanocomposites for tyre application

Abstract: A novel carbon black (CB) and nanoclay (NC) dual phase‐filled system in SBR matrix has been developed to be employed as a tyre tread compound with optimized performance properties. The nanocomposite has shown improved dynamic properties i.e. rolling resistance (tan δ at 60°C) and wet skid resistance (tan δ at 0°C), for relatively lower loading of NC (3 phr). However, the mechanical properties and wear resistance combined with above mentioned dynamic properties have been further improved by direct substitution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 16 publications
3
16
0
1
Order By: Relevance
“…As seen in Figure 2, the SBR/10GTR compound has the overall best performance, since the wet grip and rolling resistance are their maximum and minimum, respectively. These results suggest that small amounts of GTR (10 phr) are well dispersed in the SBR matrix enhancing the rubber-filler interactions [34]. Similar results were found by Kim et al [35].…”
Section: Dynamic-mechanical Analysissupporting
confidence: 87%
See 2 more Smart Citations
“…As seen in Figure 2, the SBR/10GTR compound has the overall best performance, since the wet grip and rolling resistance are their maximum and minimum, respectively. These results suggest that small amounts of GTR (10 phr) are well dispersed in the SBR matrix enhancing the rubber-filler interactions [34]. Similar results were found by Kim et al [35].…”
Section: Dynamic-mechanical Analysissupporting
confidence: 87%
“…Hence, the presence of NR (which is a very low hysteresis rubber) in the GTR composition could also be a key factor improving the performance in terms of rolling resistance [36]. Nonetheless, at higher GTR loading (20 and 30 phr), the formation of agglomerated structures seems to dominate versus the increased amount of NR, leading to higher values of tan δ at 60 • C, and hence a higher rolling resistance [34]. Other authors have also found that the filler dispersion is the dominant factor governing the rolling resistance of vulcanizates [37].…”
Section: Dynamic-mechanical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Since some of the polymer molecules remain intercalated within the clay galleries, it may allow the slippage of rubber molecules leading to an increase in the EB (%) values of the nanocomposites compared to control compound A, which is consistent with our earlier published literatures [17][18]. The compounds B & C show an optimum balance between physical properties.…”
Section: Steel Cord Skim Compound For Radial Tyre Based On Naturalsupporting
confidence: 80%
“…Thus, silica has played a more and more important role in preparing green tire tread materials . With excellent reinforcement and abrasion resistance, carbon black (CB) is also one kind of indispensable filler for the preparation of tire tread materials . Furthermore, star‐shaped solution‐polymerized styrene–butadiene rubber (SSBR) with end groups coupled by SnCl 4 has many characteristics, including a low internal friction loss, few free macromolecular terminals, and good wet traction.…”
Section: Introductionmentioning
confidence: 99%